Promoting future work skills in vocational training and baccalaureate setting through engagement in volunteering - Olmos-Gómez, María del Carmen; García-Garnica, Marina; Romero-Díaz de la Guardia, Jose Javier (Frontiers in Education, 2022)
The aim of the present study was to analyse differences in future work skills as a function of participation in volunteering and work. The present study was based on a total sample of 3101 students enrolled in secondary and baccalaureate education and vocational training in Andalusia (Spain). Once the quality parameters of the instrument were determined, its reliability and validity were confirmed, and data collection was initiated. With regards to data analysis, multivariate analysis (ANOVA) was conducted which interacted the variable describing engagement in volunteering and the variable pertaining to employment, with both variables having two levels (yes-no). From the data obtained, it was concluded that working or having worked at some point in time was particularly related with aspects related to intelligence linked with the society in which work is carried out. Other conclusions were that workers and volunteers possessed better competency attributions, knowledge of new means of communication and multidisciplinary skills. These outcomes were related with a series of motivations such as professional development, personal growth and putting their abilities into practice in order to improve their professional career.